Faktor-Faktor yang Mempengaruhi Kelengkapan Imunisasi Dasar Pada Bayi Usia 12 Bulan di Masa Pandemi Covid-19 - Siti Lis Jarsiyah; Christin Angelina Febriani; Wayan Aryawati (Jurnal Kesehatan Komunitas, 2023)
Complete basic immunization consists of 1 dose of hepatitis B, 1 dose of BCG, 3 doses of DPT-HB-Hib, 4 doses of polio drop, and 1 dose of measles. The target for complete basic immunization in 2019 is 93% with a complete basic immunization achievement of 57.9%. The impact of not getting complete immunization is the incidence of morbidity and mortality due to tuberculosis, poliomyelitis, measles, hepatitis B, diphtheria pertussis, and tetanus neonatorum. This study aims to find out factors that affect the completeness of basic immunization for infants aged 12 months old during the COVID-19 pandemic in the Gunung Sari Health Center Work Area, Way Khilau District in 2022. This research is quantitative with a cross-sectional design. The population in this study were all mothers who had infants aged 12 months old in the working area of ​​the Gunung Sari Health Center. The sample in this study were 81 peoples. The sampling technique was purposive sampling. Data analysis was analyzed using univariate, bivariate, and multivariate analysis. The results of this study indicate that there was a relationship between maternal age (p = 0.000), education (p = 0.000), knowledge (p = 0.001), family support (p = 0.003), and support from health workers (p = 0.042) with the completeness of basic immunization for infants aged 12 months old during the Covid-19 pandemic. The most dominant factor in influencing the completeness of basic immunization in infants aged 12 months old was the knowledge variable. Suggested for mothers can be more active in seeking information about basic immunizations that should be given to children so that no more children have incomplete immunization status.